“The Spirit of Truth” as a guide in John 16,12-15 - Karczewski, Marek (Studia Warmińskie, 2012)
The Situation of the Church in the contemporary Time is very difficult. Rejection, negation, indifference to her Mission conduct to discouragement and impotence in work. The last prediction of Paraclet in John 16,12-15 give us a indication and hope. The true power of Church is fidelity and maintenance in Christ. The best guide into the faith is the “Spirit of Truth”. He guides to Jesus Christ, Son of God, Savior of Man.